Dual‐interference filtering method for the main lobe based on polarimetric monopulse radar. Issue 16 (15th June 2022) - Lu, Dongwei; Wang, Yufei; Ma, Jiazhi; Feng, Dejun
Abstract: In the field of target tracking, monopulse radar is widely used to obtain the positions of radar targets. The achieved angle measurement performance is greatly weakened when barrage interference is contained in the main lobe of the receiving antenna. Interference signals can be easily filtered by the conventional polarization filtering (PF) method. However, the conventional PF method is unable to address situations in which two barrage interferences with different polarization states are contained in the main lobe, because the polarizations of both interferences become complex. To filter dual‐interference sources in the main lobe, a novel polarimetric filtering method is proposed in this letter. This novel method is based on polarization selection, which is implemented to suppress one of the dual‐interference sources. The appropriate polarimetric parameters are first selected by a monopulse ratio constraint condition. Then, the spatial location of the other interference source can be measured. After searching the whole polarimetric domain, the spatial parameters of the two interference sources can be acquired by the polarimetric monopulse system. Finally, the waveforms of the interference signals can also be estimated during the filtering process. The results of a microwave chamber experiment demonstrate that this novel filtering method is effective.